If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(5-x)-3(x-6)=-2
We simplify the equation to the form, which is simple to understand
2(5-x)-3(x-6)=-2
Reorder the terms in parentheses
+(+10-2x)-3*(x-6)=-2
Remove unnecessary parentheses
+10-2x-3+*(+x-6+)=-2
Reorder the terms in parentheses
+10-2x+(-3x+18)=-2
Remove unnecessary parentheses
+10-2x-3x+18=-2
We move all terms containing x to the left and all other terms to the right.
-2x-3x=-2-10-18
We simplify left and right side of the equation.
-5x=-30
We divide both sides of the equation by -5 to get x.
x=6
| 3v+5+2v=x-21 | | 12x-3(x+5)=-2 | | 2x+3(x+4)=-3 | | 2(x+3)=3(x-3) | | -7x^2+28=0 | | 3=10x-7 | | 3(2x-4)-6-3x=12 | | 8x+4(x-2)+4(x-1)=68 | | 3+7(2x-3)=4x+12 | | -7y=6y+10 | | a/6=8/18 | | -9=5x+21-3x | | 4=2(x-1) | | x/6-12=-12 | | 2x+7=5x-14 | | 3(x+4)+10=45 | | 2.7/2862= | | 4q^2-16q^2=0 | | 7(x+4)=-14 | | -5x=18 | | -5=18 | | 4(5x+3)=(7x+6) | | x^2+5x+2=-2x^2 | | x+1/2=3/4 | | 8x^2+10+3=0 | | 140x^2+300x=-40x-120 | | -7(5-6m+n)= | | -2w+7=-w | | 2ln(x)-ln(2x-1)=0 | | 2ln(x)=ln(2x-1) | | 3(5y+9)-2(y+9)= | | 3*6-2x=-54 |